Prognostic Observational Analysis of BMI, Leptin, and Adiponectin in Children With Acute Lymphocytic Leukemia Undergoing Remission-Induction Chemotherapy - Jing Sun; Ru Zhang; Jianjun Tang; Xuedong Wu; Lu Zhu; Haiying Huang; Huimin Chen; Minhua Xiao; Hongfeng Luo; Haiqing Zheng; Jiaqi Chen (Frontiers Media S.A., 2022)
BackgroundThe survival rate of children and adolescents with acute lymphoblastic leukemia (ALL) has progressively improved. However, ALL survivors often have adverse effects after treatment, such as an increased risk of obesity. Obesity has been associated with reduced survival.ObjectiveWe investigated the relationship between obesity, adipocytokine levels, and ALL short-term outcomes.MethodsWeight and height were measured, and body mass index (BMI) was calculated at patient diagnosis and discharge. Leptin and Adiponectin levels and Minimal Residual Disease (MRD) were measured before therapy, at days 19 of remission-induction therapy, and at the end of remission-induction therapy (days 46). The relationship between BMI, adipocytokine levels, and MRD was then determined.ResultsCompared to the normal BMI group, children with an abnormal increase in BMI had an increase in MRD at day 19 and 46 (P = 0.04 and P = 0.008), and showed a positive correlation (P = 0.014). In addition, we found a positive correlation between weight, hip circumference at diagnosis and at day 19, and MRD at day 46. Both BMI and fat concentric distribution affected the outcome of ALL children. A higher BMI was also associated with a significant increase in Leptin levels at diagnosis. Leptin resistance should be considered in ALL children with high BMI.ConclusionBMI affects the outcome of ALL patients. Early interventions such as regular weight, height monitoring, and dietary assessments should be preferably initiated during remission-induction chemotherapy.